Role of saphenoperitoneal shunt in management of refractory ascites - Ibrahim SMA,; Harunarashid H, (Department of Surgery, UKM Medical Centre, 2011)
Refractory ascites is difficult to treat by restriction of salt and repeated paracentesis which have been the mainstay of treating it for a long time. Sapheno-peritoneal shunts have been performed in patients with refractory ascites . Here, we evaluated the use of saphenous vein to be anastomosed to the peritoneam to drain the refractory ascites. Nine patients (7 male, median age 45 years, range 17 - 69) with tense refractory ascites associated with liver cirrhosis, perioprtal fibrosis and end stage renal diseases underwent sapheno-peritoneal anastomosis by mobilizing and rotating the proximal vein in order to be anastomosed to peritoneum in the lower abdomen . All procedures were performed under local anaesthesia. Thirty-day mortality was 22% (2) patient. Morbidity included fluid leakage in 1 (11%), and wound infection in 1 (11%). Hospital stay (median) was 16 days (range 11 to 23). In the short term (median of 2 months) significant reduction in body weight and abdominal girth was seen in 9 (90%), 6 (60%) were not on diuretics while 3 (30%) continued to remain on reduced doses of diuretic. Furthermore, 7 (70%) did not require paracentesis. At 2-year follow-up, 5 (45%) patients died and 3 succumbed during follow-up. The remaining 3 were all in active employment, 1 was off diuretics, and 2 were on reduced doses. All 3 patients maintained reduced body weights and abdominal girths compared with preoperative values. Saphenous-peritoneal shunt appears a simple, safe, and cost effective method of achieving long-term control of refractory ascites. The use of autogenous shunt is an added advantage over prosthetic shunts for drainage of ascitic fluid.